FACTORS RELATED TO THE INCIDENCE OF EYE FATIGUE TO COMPUTER EXPOSURE IN WORKERS AT PT. A. W FABER-CASTELL INDONESIA BEKASI IN 2022 - Fidela Angelina Hafiz; Triana Srisantyorini; Dihartawan; Januar Ariyanto (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
The use of computers is useful as a communication tool, facilitating work. Excessive use of computers can cause eye disease, body, or head. Globally, around 45-70 million people spend time watching videos. basic health research in 2018, the proportion of eye injuries caused by an event or accident in the productive age of 15-45 years was 2.6%. As for the type of employee work, eye injuries have a proportion of 0.5 %. The purpose of this study was to determine the factors associated with the incidence of eye fatigue due to computer exposure among workers at PT. AW Faber-Castell Indonesia Bekasi Year 2022. This type of research uses analytic research with a cross-sectional approach with a total sample of 50 workers at PT. AW Faber-Castell Indonesia. The sampling technique uses the Total Population. Data were analyzed univariately and bivariately with the Chi Square test. The results of this study indicate workers who experience eye fatigue (74%). The most common types of eye fatigue are blurred vision (42%), sore eyes (32%), and difficulty focusing to see (30%). In this study, there were no variables that had a significant relationship, namely the distance on the monitor screen with a p-value = 0.303, eye rest P- value = 0.886 (p-value>0.05) OR = 0.735 (95% CI = 0.202-2.674), duration of computer uses p-value = 1000, work period p -value = 0.707, lighting p -value = 1000. There were many complaints of eye fatigue and duration of computer use that exceeded 4 hours/day. So, it is recommended to pay attention to the risk of eye fatigue by stretching to rest the eyes work with lighting appropriate to the type of work object, and carry out maintenance.